2010
DOI: 10.3390/ijms11093226
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Application of 1-D Cerium Oxide Nanomaterials: A Review

Abstract: The present work provides a comprehensive overview of the recent progress of research work toward developing new one dimensional (1-D) ceria (CeO2) nanomaterials. The review has been classified into three parts: the preparation procedures with identification of the existing different dimensional ceria nanomaterials, the formation mechanisms, and an analysis of their applications. From literature survey, it is inaugurated that the fundamental structures of the ceria nanomaterials constructively dominate their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(64 citation statements)
references
References 73 publications
1
59
0
Order By: Relevance
“…At room temperature, the reaction of cerium(III) nitrate under basic conditions with ammonia results in the precipitation of gelatinous hydrous cerium(IV) oxide [7]. When ammonia is added to a cerium(III) precursor solution, immediate precipitation of Ce(OH) 3 is observed because of the low solubility constant of this compound (K sp = 7 × 10 −21 ) [13].…”
Section: Tentative Mechanism Of Particle Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…At room temperature, the reaction of cerium(III) nitrate under basic conditions with ammonia results in the precipitation of gelatinous hydrous cerium(IV) oxide [7]. When ammonia is added to a cerium(III) precursor solution, immediate precipitation of Ce(OH) 3 is observed because of the low solubility constant of this compound (K sp = 7 × 10 −21 ) [13].…”
Section: Tentative Mechanism Of Particle Formationmentioning
confidence: 99%
“…Most of the advanced applications of CeO 2 generally appear in the nanosized regime, in which many physical properties are strongly size dependent and show significant quantum size effects. Many new potential applications for nanometric ceria-including solar cells, nanolasers, and other highly functional and effective devices-are under current discussion [7]. The synthesis of nanosized ceria particles have been achieved by many different methods.…”
Section: Introductionmentioning
confidence: 99%
“…Lin and Chowdhury [17] demonstrated the application of a well-known hydrothermal synthesis technique at a higher concentration of sodium hydroxide (pH >10). This method was conducted for 24 hours and successfully produced 1-D nanorod structure with 20-40 nm and 200-300 nm of diameter and length, respectively.…”
Section: +mentioning
confidence: 99%
“…and other authors reported the similar red shift in wavelength with the increase in Ce 3+ concentration. [52][53][54] The band gap of undoped and europium doped CeO2 samples are calculated from UV-Vis spectra and listed in Table 2.…”
Section: Dopant Ion Concentration By Txrfmentioning
confidence: 99%